Environmental cues regulate epigenetic reprogramming of airway-resident memory CD8+ T cells - Hayward, Sarah L.; Scharer, Christopher D.; Cartwright, Emily K.; Takamura, Shiki; Li, Zheng-Rong Tiger; Boss, Jeremy M.; Kohlmeier, Jacob E. (Nature immunology, 2020)
Tissue-resident memory T cells (T RM cells) are critical for cellular immunity to respiratory pathogens and reside in both the airways and the interstitium. In the present study, we found that the airway environment drove transcriptional and epigenetic changes that specifically regulated the cytolytic functions of airway T RM cells and promoted apoptosis due to amino acid starvation and activation of the integrated stress response. Comparison of airway T RM cells and splenic effector-memory T cells transferred into the airways indicated that the environment was necessary to activate these pathways, but did not induce T RM cell lineage reprogramming. Importantly, activation of the integrated stress response was reversed in airway T RM cells placed in a nutrient-rich environment. Our data defined the genetic programs of distinct lung T RM cell populations and show that local environmental cues altered airway T RM cells to limit cytolytic function and promote cell death, which ultimately leads to fewer T RM cells in the lung. Kohlmeier and colleagues showed that the airway environment drove transcriptional and epigenetic changes that regulated the cytolytic functions of airway T RM cells and promoted their apoptosis due to amino acid starvation and activation of the integrated stress response.